Cryptococcus neoformansisolates from Yaoundé human immunodeficiency virus‐infected patients exhibited intra‐individual genetic diversity and variation in antifungal susceptibility profiles between isolates from the same patient. Issue 7 (July 2016) - Kammalac Ngouana, Thierry; Drakulovski, Pascal; Krasteva, Donika; Kouanfack, Charles; Reynes, Jacques; Delaporte, Eric; Boyom, Fabrice Fekam; Mallié, Michèle; Bertout, Sebastien
Abstract : N/A: Cryptococcal meningitis is a dreadful opportunistic fungal infection amongst human immunodeficiency virus (HIV)‐infected patients. One complication in the management of the disease is the possible infection of a patient by two or more different strains of Cryptococcus neoformans. This study investigated the intra‐individual genetic diversity and antifungal susceptibility of C. neoformans isolates from Yaoundé (Cameroon) HIV‐infected patients with cryptococcal meningitis. Twenty‐five clinical isolates were obtained during a prospective study. Five colonies were randomly collected from each initial sample. The 150 isolates obtained (125 colonies and 25 initial samples) were submitted to serotyping by multiplex PCR. Genotyping analyses were achieved using RFLP, and minisatellite‐ and microsatellite‐length polymorphism. The antifungal susceptibility testing was carried out using a Sensititre YeastOne kit. Seven antifungals were tested: itraconazole, fluconazole, amphotericin B, ketoconazole, 5‐fluorocytosine, posaconazole and voriconazole. The 150 isolates were identified as C. neoformans serotype A and genotype VNI. The microsatellite and minisatellite sequence analyses generated 15 genotypes. Six out of 25 (24 %) patients were found to be infected by two different genotypes. Antifungal susceptibility showed several profiles: posaconazole (0.015‐0.25 μg ml −1 ), amphotericin B (0.06‐1 μg ml −1 ), fluconazole (0.5‐16 μg ml −1 ), itraconazole (0.008‐0.12 μg ml −1 ), ketoconazole (0.008‐0.12 μg ml −1 ), 5‐fluorocytosine (0.25‐16 μg ml −1 ) and voriconazole (0.008‐0.12 μg ml −1 ). It was noted that isolates from the same patient might present different susceptibility profiles to an antifungal drug with differences of more than four dilutions. The results achieved highlighted the possible presence of isolates with different genotypes in a patient with dissimilar antifungal susceptibility profiles during a single episode of cryptococcal meningitis.